The Urgency of Applying Insolvency Test on General Corporate Bankruptcy under the Regime of Law Number 37 of 2004 - Silalahi, Udin; Lo, Adeline; Chen, Natasya Edgina; Baretta, Nicole (SIGn Jurnal Hukum, 2025)
Unlike the financial sector, which has been modernized through Law Number 4 of 2023, the bankruptcy regime for general corporate entities in Indonesia remains confined to formalistic requirements. This is rooted in Article 2 section (1) of Law Number 37 of 2004, which adopts the principle of presumption of insolvency, allowing a company to be declared bankrupt with merely two creditors and one matured debt. This process may occur without a material assessment of financial condition. This condition creates a legal loophole that allows creditors to misuse bankruptcy instruments as an aggressive debt-collection tool. This practice can result in solvent companies being terminated, as evidenced by the case analysis of PT Sritex, which was ultimately declared bankrupt. This study aims to analyze the urgency of applying the insolvency test as a substantive requirement for general corporate bankruptcy. Furthermore, this research examines the juridical obstacles to its implementation within the commercial court system. The research method employed is normative legal research using statute, conceptual, and comparative approaches regarding the Insolvency Act 1986 (UK) and the Bankruptcy Code (US). The results conclude that the primary obstacle to adopting the insolvency test is the conflict with the principle of summary proof (sumir) in Article 8 section (4) of Law Number 37 of 2004. Therefore, this study recommends legal reform through a hybrid approach. This model combines the cash flow test as an entry point and the balance sheet test as a defense mechanism. Another recommendation is the shifting of the burden of proof to the debtor to prove its solvency. This step aims to realize economic justice and prevent premature bankruptcy.